Design and construction of air temperature and relative humidity measurement system in solar dryer using Android operating system - Ornanong Sanorchit (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to design and create air temperature and relative humidity measurement system for solar dryer. Solar dryer used in this research created by Physics Program, Faculty Science and Technology, Thepsatri Rajabhat University. After creating the measurement system, the measurement system was installed inside solar dryer and temperature and relative humidity were measured by using this system. Blynk application which is a mobile application on Android operating system. The measurement system can be opearated real time and the data can be exported in Excel file. To do this, ESP8266 and DHT22 were connected with Blynk application. The measurement system was used to measured temperature and relative humidity inside solar dryer. The temperature value inside solar dryer is between 51.517 to 56.22 ๐C, relative humidity value is between 6.143 to 12.154 % For the outside solar dryer, temperature is between 44.949 to 42.1 ๐C and relative humidity is between 9.891 to 12.382 %. Using a microcontroller form Blynk application compared with a standard measuring instrument that is used is Data Loggers of HIOKI form Japan. Where when comparing, there is an error of 0.5%